MODELING BLAST LOAD FOR PREDICTING PEAK PARTICLE VELOCITY IN BENCH BLASTING USING RS2 - Wardhani Tonang, Reza
Ground vibration is one of the environmental effects of blasting activity in the form of a dynamic load that can hurt the situation around the blast site if it exceeds the threshold value. The most widely used controlling index to determine the magnitude of the vibration strength is the Peak Particle Velocity (PPV). This study conducted modeling blast load for predicting PPV value using the finite element method with RS2 software. Modeling is done by trial-error input blasting load value in the model until the PPV value is the same as the actual PPV value. The blasting load value obtained is then analyzed using multivariate statistical analysis with blasting operation parameters that can affect the PPV value namely, the maximum explosive charge per delay time and the length of the blasting area. The results showed that the blasting load is directly proportional to the maximum explosive charge per time delay and inversely proportional to the length of the blasting area. To evaluate this relationship, a comparison of the predicted PPV value from numerical modeling and empirical equations was carried out with the actual PPV value. The results show that the PPV value from numerical modeling has the best Mean Absolute Error (MAE), Root Mean Square Error (RMSE) and coefficient of determination (R2). So, it can be concluded that the blasting load equation obtained can be used in predicting the PPV value that is accurate and close to the real conditions in the field.